Can chronotropic incompetence predict life-threatening ventricular arrhythmias in patients with stable ischemic heart disease? - Yelena Rib; Gulnar Zhussupova; Gaukhar Igimbayeva; Ayan Abdrakhmanov; Seyedfarzad Jalali (Babol University of Medical Sciences, 2018)
Background: Chronotropic incompetence has prognostic value of all-cause and cardiovascular mortality in both patients with asymptomatic and symptomatic ischemic heart disease (IHD), regardless of traditional risk factors. The aim of this study was to investigate the relationship between chronotropic response during exercise test and the development of ventricular arrhythmias. Methods: 153 patients with stable ischemic heart disease were screened and observed during the 24 months since October 2014 in a university hospital in Astana Kazakhstan. They underwent bedside electrocardiography, 24h heart rate Holter monitoring, echocardiography, exercise stress test (treadmill) for assessment of chronotropic index calculating at first contact. Holter- electrocardiography was repeated three times (at 3, 6, 12 months of follow-up period) to reveal life-threatening ventricular arrhythmias. Results: The quantity of the ventricular extrasystoles was higher in the group with low chronotropic index. Low chronotropic index increased the risk of high grade ventricular extrasystoles more than two times (P=0.015); episodes of non-sustained VT more than three times (p<0.001); and episodes of sustained VT more than nine times (p<0.001). Conclusions: Chronotropic index less than 35.6 increases the risk for life-threatening ventricular arrhythmias in patients with stable chronicle ischemic heart disease irrespectively of severe left ventricle systolic dysfunction.